O sistema heterárquico e a nova autopoiese das empresas transnacionais - Parreira, Liziane (2024)
This thesis intends to analyze, based on Niklas Luhmann's systems theory, the existence of a new form of legal structure: the heterarchical system. To develop the research, the concept of the modern State was studied with Machiavelli, Hobbes and Locke. It was observed that the normativity of transnational companies goes beyond the classic concepts of State, legal order and hierarchical system brought by Hans Kelsen, Mario Losano and Luhmann. The research investigates a possible new communication between the different legal systems to define the place that the transnational company occupies in this new scenario of globalization. With the insertion of new technologies, the lex mercatoria, the set of international human rights protection, we have an interconnected society, a society of hypercommunication. There is global governance in which the role of the State has been reduced and other forms of organization have been established, given the transnational order. Such a transnational legal order will be called a heterarchical system, a concept that intersects with the hierarchical system and the systems theory of Thomas Vesting and Gunther Teubner. The confusion between public and private space is typical of globalization, which finds no barriers and breaks with the sovereignty of States. The idea that the company works autopoietically and that the government should not exceed the contours of the market has increased the proliferation of transnational companies and speculative capital. A possible solution is sought through the proposition of a new state system that is not restricted by borders, incorporating the principles of state sovereignty in the context of economic globalization.